2001
DOI: 10.1002/jnr.10112
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes in quinolinic acid‐lesioned rat striatum detected non‐invasively by in vivo 1H NMR spectroscopy

Abstract: Intrastriatal injection of quinolinic acid (QA) provides an animal model of Huntington disease. In vivo 1 H NMR spectroscopy was used to measure the neurochemical profile non-invasively in seven animals 5 days after unilateral injection of 150 nmol of QA. Concentration changes of 16 metabolites were measured from 22 l volume at 9.4 T. The increase of glutamine ((ϩ25 Ϯ 14)%, mean Ϯ SD, n ϭ 7) and decrease of glutamate (Ϫ12 Ϯ 5)%, N-acetylaspartate (Ϫ17 Ϯ 6)%, taurine (Ϫ14 Ϯ 6)% and total creatine (Ϫ9 Ϯ 3%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Our 1 H spectra matched those of Tkác et al [41]. They explored the model using 1 H spectroscopy and recorded a similar set of data post injection (after five days).…”
Section: 3supporting
confidence: 62%
“…Our 1 H spectra matched those of Tkác et al [41]. They explored the model using 1 H spectroscopy and recorded a similar set of data post injection (after five days).…”
Section: 3supporting
confidence: 62%
“…The normalized NAA levels were defined as the ratio of NAA ipsi / NAA cl . We did not normalize NAA levels to total-Creatine or total-Choline levels since we could not assume that these metabolites remain constant for 49 days post QA-injection, in light of the recent reports showing changes in these metabolites already 5 days post QA-injection (21).…”
Section: Analysis Of Mrsi Resultsmentioning
confidence: 99%
“…The 3-NP model has been widely investigated by MR (12,(14)(15)(16)(17)(18). However, a comprehensive longitudinal MR study has not been performed yet on the QA model, although a few MR studies have shown the evolution of the lesion (19,20) while others have shown NAA levels in a dose response manner in one time-point (21,22). We performed in-vivo multiparametric MRI and MRSI that extended over 49 days to assess the spatial and temporal evolution of the QA neuropathology.…”
Section: Introductionmentioning
confidence: 99%
“…The [Glu]/[Gln] ratio in normal brain is an important parameter, because Glu and Gln metabolism in the brain is closely related to neurotransmission and Glu and Gln cycling between neurons and glia (33, 34). In addition, the decrease in [Glu]/[Gln] ratio from a normal value for a specific brain region and age is assumed to be a marker of a metabolic defect (35, 36).…”
Section: Discussionmentioning
confidence: 99%